KESULITAN MENYIMAK, BERBICARA, DAN MENULIS DALAM PEMBELAJARAN BAHASA INDONESIA PADA SISWA SMA - Alfa Mitri Suhara (STKIP Siliwangi, 2015)
Skills of listening, speaking, and writing is a skill that must be dominated by theIndonesian students in learning at school. Mastery of language skills listening,speaking, and writing in school we aim to make the students to have the languageskills to be productive and receptive. The objectives will be achieved whenimplementing learning activities performed well, quality, and in accordance with theobjectives to be achieved. The purpose of this study is to provide tretmen (remedial)as well as appropriate follow-up to increase the ability of students who havedifficulty in learning the language skills of speaking, listening, reading, and writing.This study uses a case study (case study). From the results of a study of samples ofunknown samples is difficult to concentrate in learning activities, still influenced bythe local language (mother tongue) under their control. It is also influential in hiswriting. In addition, samples were not yet have a basic material way the use ofpunctuation, capitalization, and conjunctions (conjunction).